Komunikasi Politik Empati dan Homofili Ganjar Pranowo - Huda, Ridwan Imamul; Fauziah, Nurul; Halimatussadiah, Siti; Gumelar, Rangga G (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2022)
Political communication has a very important role for political actors. Various approaches to political communication can be carried out, one of which is through empathetic and homophile communication. This study aims to explore how Ganjar Pranowo implements this empathetic and homophile communication. The research method used is a qualitative descriptive approach with data collection techniques through literature searches, media and social media. The research results show that Ganjar Pranowo, through his empathetic and homophile communication, has succeeded in building voter loyalty. He managed to present himself as a leader who is like ordinary people.